Assessment of crop farmers' attitude to risk and management methods in Oyo State, Nigeria - Oladipo Akanbi Sheu-Usman; Olufemi Adekunle Adedayo; Mukaila Ridwan; Johnson Isola Abiodun (Western Balkan Journal of Agricultural Economics and Rural Development, 2022)
Agricultural sector faces series of risks which befall at different frequencies. This study examined the crop farmers' attitude to risks and their management methods in Ogbomoso, Oyo State, Nigeria. Specifically, the study examined the risk attitude of farming households, and analyzed the risk management strategies adopted by farming households in the study area. A four-stage sampling method was adopted to elicit response from selected 150 farming households for this study. The dataset was analyzed with the use of descriptive and inferential statistics. Safety-First-Model (SFM) was employed to analyze the risk attitude among crop farmers. The result revealed that majority of the farming households head was male and married with the mean age of 42 years and a moderately large household size of five persons and inheritance was the prominent means of farmland acquisition. Descriptive statistics showed that high cost of labor input topped the ranking of the risk source in the study followed by high input prices. Lacks of extension advice, low crop prices, were also common. Risk management methods employed to mitigate risk by majority of the farm families was sale of assets followed by income diversification. The SFM result revealed that all the food crop farmers were intermediate risk averse.